TRANSFORMATION OF SHARIA ACCOUNTING INNOVATION: CHALLENGES AND OPPORTUNITIES IN ANALYSIS OF DIGITALIZATION ERA - Iman Supriadi (State Islamic Institute (IAIN) Tulungagung, 2023)
This paper discusses the transformation of Islamic accounting innovation in facing challenges and creating opportunities in the digitalization era. In the context of an increasingly digitally connected business, implementing Islamic accounting innovation through information technology plays an essential role for Islamic financial companies. Previous research has shown the positive impact of adopting information technology in Islamic accounting practices, including improving operational efficiency, transparency, and quality of service to customers. However, challenges still need to be addressed, such as the complexity of Islamic accounting principles, data security, and the need for skilled human resources. This study aims to analyze the challenges and opportunities in the transformation of Islamic accounting innovation in the era of digitalization and create a strategic framework to overcome the challenges and take advantage of the opportunities. This study will identify various challenges financial companies face in implementing Islamic accounting innovations in the digitalization era through a comprehensive literature review. In addition, this study will also identify emerging opportunities in terms of utilizing technology to enhance Islamic accounting practices. The results of this study will provide valuable insights for Islamic financial companies in dealing with accounting changes and innovations in the digitalization era. By understanding the challenges and creating an appropriate strategic framework, companies can optimize the benefits of transforming Islamic accounting innovation and strengthen their position in the increasingly competitive Islamic finance industry